Written premiums and paid claims and their impact on the financial solvency of Syrian insurance companies during the period /2013-2022/ (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The current research aims to clarify the role of written premiums and paid claims in determining the level of financial solvency of Syrian insurance companies during the time period 2013/2022.The study was applied to the /13/ public and private insurance companies in the Syrian Arab Republic, by analyzing the data on premiums and insurance claims, and then calculating the solvency of the insurance companies, which reflects the extent of the insurance companies' ability to fulfill their obligations towards policyholders; The methodology based on calculating the financial solvency was adopted by measuring the adequacy of the company's assets against its liabilities.The results showed: that there is a direct correlation between each of the written premiums, the paid claims, and the financial solvency of the insurance companies.In light of the results: the researcher recommends adopting an appropriate marketing policy by adopting a better policy for accepting and selecting low-cost risks, which reflects positively on the volume of insurance premiums and contributes to reducing the volume of paid claims, raising the financial solvency of insurance companies and strengthening their financial positions.